Nexus assessment for Sudan: Synergies of the water, energy and food sectors - Babiker, Babiker; Salih, Ali; Siddig, Khalid; Ringler, Claudia (Nexus Regional Dialogue Programme, 2019)
This report presents the main findings of the Nexus assessment study for Sudan. It identified Water-Energy-Food Nexus priority issues in Sudan, suggested operational guidance to align national strategies, policies and implementation plans within a national Nexus framework, identified opportunities to apply the Nexus approach, including institutional settings and capacity building needs, and suggested a series of Water-Energy-Food Nexus projects in Sudan.